PKM Pemberdayaan Siswa MA ZAHA Pakuniran Probolinggo Sebagai First Responder dalam Memberikan Resusitasi Jantung Paru (RJP) Pada Kasus Cardiac Arrest - Sholehah, Baitus; Ningsih, Nur Kholimah (PPPM Stikes Banyuwangi, 2022)
Background: Cardiac arrest is an emergency condition that can threaten human life, therefore cardiac arrest must get first aid as soon as possible to avoid death. First aid that can be done by giving Cardiopulmonary Resuscitation (CPR). Purpose The purpose of this service is to empower MA ZAHA 04 Pakuniran Students as First Responders in Providing Cardiopulmonary Resuscitation (CPR) in Cardiac Arrest Cases and the BLS rapid reaction team. Method: The method used in this service consists of a preparation stage by coordinating with partners and a service permit, followed by the implementation stage, namely by providing training to students on Cardiopulmonary Resuscitation (CPR) and the final stage, namely closing, by evaluating participants training on knowledge and skills in providing basic life support. Result: This service activity went according to expectations, as well as the participants who were very enthusiastic and attended the training wisely. Conclution: The community service carried out increases students' knowledge and skills by being able to demonstrate CPR (hand only CPR) and being able to identify signs of cardiac arrest.